2024
DOI: 10.1007/s12672-024-00901-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive pan-carcinoma analysis of ITGB1 distortion and its potential clinical significance for cancer immunity

Yuchang Fei,
Yulun Wu,
Luting Chen
et al.

Abstract: The human protein-coding gene ITGB1 (Integrin 1), also known as CD29, has a length of 58048 base pairs. The Integrin family's most prevalent subunit, it participates in the transmission of numerous intracellular signaling pathways. A thorough examination of ITGB1's functions in human malignancies, however, is inadequate and many of their relationships to the onset and development of human cancers remain unknown. In this work, we examined ITGB1's role in 33 human cancers. Finally, a multi-platform analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Fei et al found that ITGB1 was positively correlated with most indicators of cell proliferation in a gene co-expression study. This suggests that ITGB1 has an important role in controlling cancer metastasis and proliferation 40 . Matrix metalloproteinase-9 (MMP-9) is a Matrix metalloproteinase that helps degrade parts of the extracellular matrix and has also been found to be involved in processes such as inflammation, cancer invasion and metastasis 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Fei et al found that ITGB1 was positively correlated with most indicators of cell proliferation in a gene co-expression study. This suggests that ITGB1 has an important role in controlling cancer metastasis and proliferation 40 . Matrix metalloproteinase-9 (MMP-9) is a Matrix metalloproteinase that helps degrade parts of the extracellular matrix and has also been found to be involved in processes such as inflammation, cancer invasion and metastasis 41 .…”
Section: Discussionmentioning
confidence: 99%